Building an innovative climate: The impact of leadership and well-being on innovative work behavior in educational settings - Basar, Abdul; Kusmaningtyas, Amiartuti; Ardiana, I Dewa Ketut Raka (Edelweiss Applied Science and Technology, 2024)
Innovative work behavior is important for organizational success, influenced by leadership, engagement, and creativity. Principals lead by creating an innovative climate, leveraging technology, and encouraging student ideas. Employee innovative behavior is key to driving organizational innovation. Research shows that factors such as self-efficacy, empowering leadership, and well-being play an important role in enhancing innovative behavior, which in turn can improve the quality of education and the work environment. This study examines the effect of empowering leadership on teacher innovation, highlighting the mediating role of self-efficacy and its interaction with well-being. This study uses a quantitative approach with a moderated survey design. The sample in this study consisted of 165 respondents, namely certified civil servant teachers at public junior high schools throughout Kediri Regency, taken using the Slovin method with a margin of error of 0.075. The research procedure includes testing data quality through validity and reliability using Smart PLS. Validity is tested with Pearson Correlation (>0.138) and reliability with Cronbach Alpha (>0.400). Convergent validity and AVE are also tested to ensure the measuring instrument is effective. Discriminant validity, inner model, and hypothesis testing using T-table (>1.96) are important steps. The results are expected to provide in-depth insights into teaching innovation and recommendations to improve the motivation and teaching practices of civil servant teachers in public junior high schools. This study aims to create a productive and innovative learning atmosphere. This study shows that Empowering Leadership (X2) has no significant effect on Innovative Work Behavior (Y) with Original Sample (O) = -0.037, T = 1.014, and P = 0.311. In contrast, Work Self-Efficacy (X1) shows a strong positive effect with O = 0.593, T = 9.233, and P = 0.000. The interaction between Empowering Leadership (X2) and Wellbeing (M) is not significant (O = 0.011, T = 0.386, P = 0.700), and the direct impact of Wellbeing (M) on innovation is also not visible (O = 0.020, T = 0.576, P = 0.565). However, Work Self-Efficacy (X1) significantly affects Innovative Work Behavior (Y) with a value of O = 0.964, T = 52.013, and P = 0.000. The interaction between Work Self-Efficacy (X1) and Wellbeing (M) is also not significant (O = 0.015, T = 0.606, P = 0.545). The mediation path shows that Work Self-Efficacy (X1) significantly mediates the relationship between Empowering Leadership (X2) and Innovative Work Behavior (Y) with a value of O = 0.571, T = 8.746, and P = 0.000. This study suggests the development of Work Self-Efficacy among civil servant teachers of junior high schools in Kediri Regency to improve innovation.